De l’eau de pluie à l’eau du robinet : étude d’une transformation discrète dans le Sertão (Brésil) - Anne-Laure Collard (VertigO)
In the 1990s, the Brazilian State and the World Bank promoted the "modernization" of the access to drinking water in rural communities in the Northeast region as one of the solutions to development. Thousands of distribution networks were thus implemented, complementing a technical system already in place and managed locally. Based on a field survey conducted between 2009 and 2011, this article aims to examine the social transformations brought about by the inscribing of this new artefact in three rural communities. This study analyses the reinvention of social practices around water in a territory restructured by the materiality of the new distribution network. The article shows how the advent of this local technical solution subtly reshapes the daily life of the communities and their relationship with water, and discusses the question of the future of water resource management at the scale of rural communities.